RENAL AND CORONARY PREDICTORS OF POST-MYOCARDIAL REVASCULARISATION PROGNOSIS IN PATIENTS WITH CORONARY HEART DISEASE - M. M. Batyushin; E. S. Levitskaya; V. P. Terentyev; A. A. Savis’ko; A. A. Dyuzhikov; Ya. V. Kulikovskikh (Российский кардиологический журнал, 2012)
Aim. To assess the impact of renal and local coronary risk factors (RFs) on cardiovascular survival in patients with coronary heart disease (CHD) before and after myocardial revascularisation. Material and methods. The study included 90 CHD patients with indications for myocardial revascularisation. In all participants, the presence of renal RFs (microalbuminuria (MAU) and increased levels of β2 -microglobulin (β2 -MG)) was assessed at different intervention stages. In addition, the number of coronary arteries (CA) affected by atherosclerosis, as well as CA atherosclerosis severity, was assessed. Results. Among the majority of CHD patients with myocardial revascularisation indications, MAU was observed at all intervention stages. The endpoint incidence was associated with MAU, β2 -MG levels, the number of CA affected by atherosclerosis and CA with hemodynamically non-significant stenosis. The levels of β2 -MG significantly correlated with atherosclerotic plaque growth rate. Conclusion. The increased risk of coronary events was associated with elevated levels of MAU and β2 -MG and the increased number of CA affected by atherosclerosis and CA with hemodynamically non-significant stenosis. Elevated CV risk was linked to β2 -MG levels of ≥0,1 ng/ml. The levels of β2 -MG increased in parallel with the CHD progression.